MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI POKOK FUNGSI MELALUI STRATEGI PEMBELAJARAN THE POWER OF TWO PADA SISWA KELAS VIII-1 SMPN 1 RAMBAH TAHUN PELAJARAN 2012/2013 - Yelli, Almi (Universitas Pasir Pengaraian, 2014)
This research of background overshadow by the lowering of result learn student and awareness of teacher to apply a study model which was inovatif. This research is Research Action Class. Result of perception analysed descriptively narrative with aim to to isn't it concerning student activity and teacher during study process take place, while tes result of learning to be analysed with analysis attainment of Complete Criterion of Minimum (KKM) to know there or him don’t the make-up of result learn student before and after applying of strategy study of The Power Two of. Result of research show the existence of improvement of result learn class student mathematicsof VIII5 SMPN 1 Rambah Kabupaten Rokan Hulu.